Ethnic discrimination during résumé screening: Interactive effects of applicants' ethnic salience with job context. (July 2017) - Derous, Eva; Pepermans, Roland; Ryan, Ann Marie
Systematic research considering job context as affecting ethnic discrimination in hiring is limited. Building on contemporary literature on social categorization and cognitive matching, the interactive effect of context characteristics (client contact; industry status) and person characteristics (i.e. ethnic cues: Maghreb/Arab vs Flemish-sounding name; dark vs light skin tone) were investigated using an experimental field study among 424 white majority HR professionals. Findings showed that equally qualified applicants with a dark skin tone received lower job suitability ratings than applicants with a light skin tone, particularly when they were screened for high client contact/low industry status positions and low client contact/high industry status positions. It is concluded that some ethnic cues (such as skin tone) may be more salient compared with other cues and that job context may influence the salience of ethnic cues and steer hiring discrimination in subtle ways. Implications of these findings for hiring discrimination research and organizations are discussed.